ANALISIS PERTUMBUHAN PENERIMAAN PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR TERHADAP PEMELIHARAAN DAN PERLUASAN JALAN DI KABUPATEN PURWAKARTA - Fitri Fitri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The purpose of this study is to determine the growth and contribution of revenue sharing for Motor Vehicle Taxes to Road Maintenance and Expansion in Purwakarta, as well as the growth and contribution of revenue sharing from Motor Vehicle Title Transfer Fees to Road Maintenance and Expansion in Purwakarta. from 2015 to 2019. This research method is descriptive research. The results show that the growth of motor vehicle tax revenue each year has increased along with this the growth of road maintenance and expansion in Purwakarta in 2015-2017 also increased while in 2018 it had a decrease. This is due to the APBD Allocation budgeted from the agency, there is a budget reduction and increased again in 2019 Until now, the motor vehicle tax revenue sharing has not been able to meet the needs for maintenance costs and road expansion, negative and in the following year had positive growth and growth. Road maintenance and expansion in Purwakarta in 2015-2017 experienced positive growth while in 2018 it had a decline. This is due to the budget allocation from the agency that budgeted for a reduction in the budget and increased again in 2019. Until now, the profit sharing of the Transfer of Names for Motorized Vehicles has not been able to meet the needs of road maintenance and expansion costs.